A review of projections of demand and supply of livestock-derived foods and the implications for livestock sector management in LSIL focus countries. - Enahoro, Dolapo K.; Njiru, Nelly M.; Thornton, Philip K.; Staal, Steven J. (2019)
National planners and others in the international development community are looking to transform a rising demand for animal-source foods in many low- and middle-income countries into opportunities that benefit poor and vulnerable people. Scenario analysis and sectoral reviews aid the understanding of emerging opportunities and the potential of existing systems to harness them. An analysis was done of country-level results of a global model simulating the production and consumption to 2050 of livestock-derived foods under various scenarios of economic and climate change. The scenario results were assessed alongside historical data and relevant national policies of the livestock sectors of selected countries, to identify key entry points for further pro-poor livestock sector development. While increased focus on trade in livestock and livestock products seems rationale for some countries in the study, climate change and sustainability are given more prominence for others. The results provide context to planned stakeholder engagements on national programs and policies affecting livestock in the study countries.